Karakteristik Sensori Cascara Arabika dan Robusta Asal Nusa Tenggara Barat Menggunakan Metode Rate-All-That-Apply dan Product Characterization: Sensory Characteristics of Arabica and Robusta Cascara from West Nusa Tenggara Using the Rate-All-That-Apply Method and Product Characterization - Lalu Danu Prima Arzani; Indah Nalurita; Destiana Adinda Putri (Jurnal Teknologi dan Mutu Pangan, 2026)
Cascara, a by-product of coffee processing, can be developed into value-added products and possesses unique sensory characteristics. However, quantitative studies on cascara’s sensory attributes remain limited. This study aimed to map the sensory characteristics of Arabica and Robusta cascara from various locations in West Nusa Tenggara (NTB) using the Rate All That Apply (RATA) method and the Product Characterization (PC) method. Sensory attribute descriptors were established through Focus Group Discussion with trained panelists, followed by consumer testing of eight attributes with 100 participants. The RATA results indicated that Robusta cascara from the Rinjani and Tambora varieties exhibited a high intensity of sour taste, Arabica cascara from the Tambora variety showed strong bitterness, while Arabica cascara from the Rinjani variety showed strong sweetness along with green and earthy aromas. Product Characterization (PC) analysis confirmed that the sensory profile of Arabica cascara from the Rinjani variety was dominated by sweetness and green aroma, whereas Arabica Tambora emphasized bitter and earthy notes. Robusta Rinjani cascara tended to be balanced without extreme attributes, in contrast to Robusta Tambora, which was more acidic and dry. The integration of RATA and PC methods has proven for mapping cascara sensory profiles comprehensively and systematically.